Does Financial Information Influence The Behavior of Stock Price? Evidences From Nepali Commercial Banks - Chalise, Dhan Raj (Saptagandaki Journal, 2022)
Financial information is the document that presents the overall financial health of the organization. This study examines the influence of financial information on stock price behavior of Nepalese commercial banks. Twelve commercial banks are selected as a sample out of total twenty-six commercial banks of Nepal based on operation more than ten years with availability of necessary information. This study utilizes quantitative research approach with causal-comparative research design. Adopting descriptive statistics and multiple regression analysis for data analysis, study found that financial information like net interest margin, net profit margin, dividend payout ratio and capital adequacy ratio have significant positive influence on determining stock price behavior of Nepalese commercial banks. In addition, evidence indicates that financial information is the major influencing factor while determining stock price and investment decision so investors should properly analyze financial information for superior investment decision.